A case of neonatal tetanus presented within 24 hours of life. (January 2013) - Chatterjee, Sayan; Hemram, Sunil; Bhattacharya, Subhasish; Khuntdar, Bidyut Kumar
Summary: Neonatal tetanus is still prevalent in developing countries such as India. Generally, neonatal tetanus is seen in babies of unimmunized mothers beyond the second day of life. A neonate presented to us on the 4th hour of birth with a periumbilical ulcer. The baby's antenatal and birth history was uneventful. The mother had been immunized against tetanus. At presentation, the baby was active, alert and sucking normally. Avery small ulcer was noted below the umbilicus. Subsequently, the baby developed rigidity and a tonic spasm of its body with recurrent seizures from the 18th hour of its birth and by 21st hour. It also had a full blown clinical picture of neonatal tetanus including: masseter spasm; generalized rigidity; a high pitched cry: and intermittent opisthotonos posturing. An ulcer gradually enlarged to 5 × 4 cm and a swab from ulcer showed Clostridium tetani (both on Gram staining and culture). A review of the published literature did not reveal any case that had presented so early. Therefore, this is probably the first case of neonatal tetanus being reported within the 21st hour of birth.